2020
DOI: 10.22206/cyed.2020.v4i1.pp47-69
|View full text |Cite
|
Sign up to set email alerts
|

¿Por qué los estudiantes de la Universidad Pedagógica ISFODOSU escogen la carrera de Educación?

Abstract: Como parte de una investigación dirigida a establecer los perfiles de los estudiantes de nuevo ingreso en ISFODOSU, incluimos variables vocacionales para determinar las motivaciones más importantes para la elección de carrera de los participantes, así como para la elección de esta universidad y la opinión sobre sus recursos tecnológicos. La muestra (N = 744) fue elegida al azar, de modo proporcional entre los estratos Recintos, Carreras y Sexo. En primer lugar, validamos la escala FIT-Choice con dos análisis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
0
2
0
7
Order By: Relevance
“…There are gender differences in this case too, since women’s perceptions are greater in terms of demanding degree programs, demanding profession, and satisfaction with choice, while men’s obtained the highest score in the salary, and social status factors. The study by Silvestre et al (2020) also indicates differences in perceptual factors, with higher ratings for girls. The research conducted by Said-Hung et al (2017) also showed that the factors related to perceptions that obtained the highest score were the views regarding the demands of the profession and satisfaction with the choice of this career.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…There are gender differences in this case too, since women’s perceptions are greater in terms of demanding degree programs, demanding profession, and satisfaction with choice, while men’s obtained the highest score in the salary, and social status factors. The study by Silvestre et al (2020) also indicates differences in perceptual factors, with higher ratings for girls. The research conducted by Said-Hung et al (2017) also showed that the factors related to perceptions that obtained the highest score were the views regarding the demands of the profession and satisfaction with the choice of this career.…”
Section: Discussionmentioning
confidence: 79%
“…It has also been proven in Bruinsma and Jansen (2010) and Yüce et al (2013) studies that altruistic motivations are greater in women and extrinsic motivations are more common among men. Similarly, the work of Silvestre et al (2020) shows that female students are more motivated to work with children and adolescents. With regard to teachers of English, Zehir-Topkaya and Uztosun (2012) reached similar conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…(1) Motivación (Hong et al, 2018;Starr et al, 2006;Zhang et al, 2016), entendida como las razones que motivan a ejercer el rol docente y permanecer en labores de enseñanza. Este constructo ha sido abordado ampliamente por investigaciones sobre los factores que influyen en la elección de carreras de Pedagogía (Fray & Gore, 2018;García-Poyato et al, 2018;Said-Hung et al, 2017;Silvestre et al, 2020;Watt & Richardson, 2007), destacando los factores de motivación intrínseca (eg. disfruto enseñar) y altruista (eg.…”
Section: Dominios De La Identidad Docenteunclassified
“…Entre los factores que conforman la motivación intrínseca, destaca el deseo y predisposición por trabajar con el colectivo infantil, las investigaciones de Marín et al (2021), Merino et al (2015), Prada et al (2021, Silvestre et al (2020) y Vilchez (2019), donde se sigue una tendencia que ya había sido identificada por autores como Revelli et al (2013) en el pasado.…”
Section: Análisis De Contenido Cualitativounclassified
“…-El prestigio de la institución: la existencia de múltiples tipos de instituciones que imparten carreras de Educación supone que unas poseen mayor prestigio que otras. El acceso a un programa de bajo prestigio suele identificarse con mayores tasas de deserción en las carreras del área educativa (Said-Hung et al, 2017;Silvestre et al, 2020;De Lima et al, 2019;Escobar, 2013).…”
Section: Análisis De Contenido Cualitativounclassified